2016
DOI: 10.1371/journal.pmed.1002188
|View full text |Cite
|
Sign up to set email alerts
|

Leukocyte Telomere Length in Relation to 17 Biomarkers of Cardiovascular Disease Risk: A Cross-Sectional Study of US Adults

Abstract: BackgroundLeukocyte telomere length (LTL) is a putative biological marker of immune system age, and there are demonstrated associations between LTL and cardiovascular disease. This may be due in part to the relationship of LTL with other biomarkers associated with cardiovascular disease risk. However, the strength of associations between LTL and adiposity, metabolic, proinflammatory, and cardiovascular biomarkers has not been systematically evaluated in a United States nationally representative population.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
114
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 139 publications
(132 citation statements)
references
References 54 publications
13
114
5
Order By: Relevance
“…In addition, Njajou et al [36] published similar findings, where a seven years follow up was associated with smaller increases in BMI and body fat in those individuals who presented longer TL. Rehkopf et al [37] in a large nationally representative U.S. sample did not find an association between MetS and shorter TL. They did not report the prevalence of MetS in their population and not stratify the individuals in accordance to the variables of MetS, as we performed in our study.…”
Section: Discussionmentioning
confidence: 91%
“…In addition, Njajou et al [36] published similar findings, where a seven years follow up was associated with smaller increases in BMI and body fat in those individuals who presented longer TL. Rehkopf et al [37] in a large nationally representative U.S. sample did not find an association between MetS and shorter TL. They did not report the prevalence of MetS in their population and not stratify the individuals in accordance to the variables of MetS, as we performed in our study.…”
Section: Discussionmentioning
confidence: 91%
“…Speculatively, the difference in telomere length across women with higher SES and younger adults, suggests a physiological age deterioration for these individuals when reporting greater exposure to particular types of discrimination. Thus, these subgroups may assume health trajectories that are paradoxical to what is expected as a function of social statuses they occupy (Rehkopf et al, 2016). In the absence of telomerase activity that would allow estimation of metric of years lost physiologically, the current findings are underscored by prior studies demonstrating that the difference in telomere length intimates impending health outcomes (Cherkas et al, 2006; Geronimus et al, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…A previous study reported that an one unit difference in the following biomarkers were associated with kilobase pair differences in LTL, such as BMI, waist circumference, percentage of body fat, HDL, triglycerides, pulse rate, systolic blood pressure and diastolic blood pressure[15]. However, these studies only focused on the relationship between individual MetS components and telomere length.…”
Section: Discussionmentioning
confidence: 99%